INVITRO ACTNITY OF METRONIDAZOL AGAINST TO H. PYLORI AS DETERMINED BYAGAR DILUTION METHOD AND INVITRO ACTNITY OF AMOXICILLIN AND CLARITROMYCIN AGAINS TO H.PYLORI AS DETERMINED BYDISK DUFFUSION METHOD - Fikret ŞAHiN; Ali ÖZDEN; Enver ÜNVER; Hatice ÖZENCİ and Özden UZUNALİMOĞLU and Gültekin ATALAY and Ömer KOÇ (Turkish Journal of Gastroenterology, 2020)
-